Knowledge and practice of nursing students regarding bioterrorism and emergency preparedness: comparison of the effects of simulations and workshop - Mahsa Ghahremani; Zahra Rooddehghan; Shokouh Varaei; Shima Haghani (BMC, 2022)
Abstract Background and purpose Bioterrorism is a global threat. Nurses are one of the first groups that should be ready for it. College years are the best time to educate these issues. This study aimed to compare the effectiveness of simulation and workshop on knowledge and practice of nursing students regarding bioterrorism. Materials and methods This was an experimental study. The study sample consisted of 40 last-year nursing students who were randomly assigned to two groups by using random numbers table. Data was collected using a demographic questionnaire, bioterrorism knowledge scale, and an OSCE checklist. Before the intervention, the students completed the study questionnaires and a six-station OSCE test. The workshop group (20 students) learned how to deal with bioterrorism through lectures. The simulation group (20 students) participated in a simulation learning program. After one month, the students completed the study tools again. Finally, collected data were analyzed using descriptive and inferential statistics in SPSS V.16. Results The difference between the knowledge and performance scores of both groups (workshop and simulation), before and after the intervention, was statistically significant (P < 0.001). Students in both groups had higher knowledge and performance scores after the intervention. The simulation group scores were higher than the workshop group scores in the knowledge and the most of performance domains. Conclusion The simulation group had better results in terms of enhancing knowledge, preparedness, disaster triage, reporting, incident management, communication, mental disorders, and isolation domains compared to the workshop group.